1999
DOI: 10.1128/iai.67.5.2531-2539.1999
|View full text |Cite
|
Sign up to set email alerts
|

Local Secretory Immunoglobulin A and Postimmunization Gastritis Correlate with Protection againstHelicobacter pyloriInfection after Oral Vaccination of Mice

Abstract: C57BL/6 mice were orally immunized with five weekly doses of 2 mg, 200 μg, or 2 μg of Helicobacter pylori (Sydney strain) whole-cell sonicate combined with cholera toxin. One week after the last vaccination, mice were challenged with 5 × 107CFU of live H. pylori three times at 2-day intervals. At 6 or 18 weeks after the challenge, mice were sacrificed and bacterial cultures and histological studies of the stomach were performed. Vaccination with 2 mg/session or 200 μg/session inhibited H. pylori colonization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 19 publications
6
43
1
Order By: Relevance
“…On the other hand, gerbils immunized with the LT R72DITH adjuvant vaccine exhibited lower titers of serum IgG but comparatively effective immune protection. These results indicated that the other immune mechanisms such as mucosal sIgA responses could be more important than the serum IgG response in immune protection against H. pylori infection, which is consistent with previous reports [6,49]. Due to the limitations of reagents for analysis of immune effector mechanisms in the Mongolian gerbil model, we could not pursue this study on mucosal sIgA response and other humoral immunity further.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, gerbils immunized with the LT R72DITH adjuvant vaccine exhibited lower titers of serum IgG but comparatively effective immune protection. These results indicated that the other immune mechanisms such as mucosal sIgA responses could be more important than the serum IgG response in immune protection against H. pylori infection, which is consistent with previous reports [6,49]. Due to the limitations of reagents for analysis of immune effector mechanisms in the Mongolian gerbil model, we could not pursue this study on mucosal sIgA response and other humoral immunity further.…”
Section: Discussionsupporting
confidence: 84%
“…All mice from the groups 1-3 were infected with ~ 10 7 colony forming units (CFU) of H. pylori (SS 1) as described previously [12]. Eight mice from each group were sacrificed at 1, 2, 4 and 8 weeks after infection except for group 1.…”
Section: Animalsmentioning
confidence: 99%
“…Histological examination (haematoxylin and eosin staining) was performed in a blinded fashion independently by two examiners. Because gastric specimens of infant mice were too small to evaluate the extent of inflammation, only the intensity of inflammation was scored on a scale of 0-3 as described previously [12]: grade 0, rare inflammatory cells; grade 1, mild; grade 2, moderate; and grade 3, severe inflammation with marked inflammatory cell infiltration.…”
Section: Inflammatory Response To H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step is thought to play an important role in steady induction of mucosal immunization. Similarly, Goto et al demonstrated that the high level of IgA observed in the stomach of mice vaccinated orally protects against infection [17].…”
mentioning
confidence: 89%